Characterization of genes with increased expression in human glioblastomas - Kavsan, V.; Shostak, K.; Dmitrenko, V.; Zozulya, Yu.; Rozumenko, V.; Demotes-Mainard, J. (Цитология и генетика, 2005)
In the present study, we have used the gene expression data available in the SAGE database in an attempt to identify glioblastoma molecular markers. Of 129 genes with more than 5-fold difference found by comparison of nine glioblastoma with five normal brain SAGE libraries, 44 increased their expression in glioblastomas. Most corresponding proteins were involved in angiogenesis, host-tumor immune interplay, multidrug resistance, extracellular matrix (ECM) formation, IGF-signalling, or MAP-kinase pathway. Among them, 16 genes had a high expression both in glioblastomas and in glioblastoma cell lines suggesting their expression in transformed cells. Other genes had an increased expression only in glioblastomas, not in glioblastoma cell lines suggesting an expression possibly originated from host cells. Many of these genes are among the top transcripts in activated macrophages, and involved in immune response and angiogenesis. This altered pattern of gene expression in both host and tumor cells, can be viewed as a molecular marker in the analysis of malignant progression of astrocytic tumors, and as possible clues for the mechanism of disease. Moreover, several genes overexpressed in glioblastomas produce extracellular proteins, thereby providing possible therapeutic targets. Further characterization of these genes will thus allow them to be exploited in molecular classification of glial tumors, diagnosis, prognosis, and anticancer therapy. Данные, имеющиеся в публичной базе данных по серийному анализу генной экспрессии (SAGE), были использованы для идентификации потенциальных молекулярных маркеров глиобластомы. 44 из 129 генов, которые проявили более чем пятикратную разницу уровня экспрессии при сравнении девяти SAGE-библиотек глиобластом и пяти SAGE-библиотек нормального головного мозга, повышали экспрессию в глиобластомах. Большинство соответствующих белков принимают участие в ангиогенезе, иммунном взаимодействии хозяин–опухоль, множественной устойчивости к лекарственным препаратам, формировании экстраклеточного матрикса, путях передачи сигнала в системе инсулиноподобных факторов роста (IGF) или МАР-киназы. Высокий уровень экспрессии 16 генов как в глиобластомах, так и в клеточных линиях глиобластом свидетельствует о том, что экспрессия этих генов происходит в трансформированных клетках. Экспрессия этих генов повышается только в глиобластомах, а не в клеточных линиях глиобластом, скорее всего в хозяйских клетках. Большинство этих генов входит в верхнюю часть списка транскриптов, активированных в макрофагах, а также вовлеченных в иммунный ответ и ангиогенез. Изменения экспрессии генов как в опухолевых, так и в хозяйских клетках, могут быть использованы как молекулярные маркеры при анализе опухолевой прогрессии астроцитарных глиом, а также для выяснения механизма заболевания. Кроме того, значительная часть генов продуцирует экстраклеточные белки, таким образом давая возможности для клинического использования. Дальнейшая характеристика генов с повышенной экспресией позволит использовать их для молекулярной классификации глиальных опухолей, диагностики, прогностической оценки и противоопухолевой терапии.